In situ phase-changeable 2D MXene/zein bio-injection for shear wave elastography-guided tumor ablation in NIR-II bio-window. Issue 24 (21st May 2020) - Zhou, Bangguo; Pu, Yinying; Lin, Han; Yue, Wenwen; Yin, Haohao; Yin, Yifei; Ren, Weiwei; Zhao, Chongke; Chen, Yu; Xu, Huixiong
Abstract : Herein, we report in situ phase-changeable 2D MXene/zein bio-injection for shear wave elastography-guided tumor ablation in NIR-II bio-window. Abstract : Localized tumor photothermal cancer ablation is a minimally invasive therapeutic modality for combating cancer, but it often suffers from low therapeutic efficacy and poor precision due to the poor accumulation and non-uniform distribution of used photothermal-conversion agents in tumor tissue via the typical intravenous administration. To address this, an injectable and phase-changeable composite bio-injection consisting of biocompatible two-dimensional (2D) niobium carbide (Nb2 C) MXene and the plant-originating protein, zein, has been engineered for near infrared (NIR)-II-triggered tumor photothermal ablation. Zein can respond to aqueous microenvironments and also external photo-triggers from the NIR-II bio-window (1064 nm), and transforms into a solid bio-implant after solvent exchange between ethanol and water. Which, thus, traps Nb2 C MXene and heat, improving ablation efficiency and enabling the precise and complete eradication of 4T1 breast tumor cells without additional safety concerns. More significantly, shear wave elastography (SWE) as a deep-penetration imaging mode that can reflect the ablated outcomes via monitoring tissue density variation, has been employed to guide the photo-thermal ablation process to further improve the ablation precision. Thus, this compatible and phase-changeable bio-injection capable of improving photo-thermal ablation efficiency holds great potential in clinical applications.